Percutaneous coronary angioplasty versus coronary artery bypass grafting in the treatment of unprotected left main stenosis: updated 5-year outcomes from the randomised, non-inferiority NOBLE trial. Issue 10219 (18th January 2020) - Holm, Niels R; Mäkikallio, Timo; Lindsay, M Mitchell; Spence, Mark S; Erglis, Andrejs; Menown, Ian B A; Trovik, Thor; Kellerth, Thomas; Kalinauskas, Gintaras; Mogensen, Lone Juul Hune; Nielsen, Per H; Niemelä, Matti; et al.
Summary: Background: Percutaneous coronary intervention (PCI) is increasingly used in revascularisation of patients with left main coronary artery disease in place of the standard treatment, coronary artery bypass grafting (CABG). The NOBLE trial aimed to evaluate whether PCI was non-inferior to CABG in the treatment of left main coronary artery disease and reported outcomes after a median follow-up of 3·1 years. We now report updated 5-year outcomes of the trial. Methods: The prospective, randomised, open-label, non-inferiority NOBLE trial was done at 36 hospitals in nine northern European countries. Patients with left main coronary artery disease requiring revascularisation were enrolled and randomly assigned (1:1) to receive PCI or CABG. The primary endpoint was major adverse cardiac or cerebrovascular events (MACCE), a composite of all-cause mortality, non-procedural myocardial infarction, repeat revascularisation, and stroke. Non-inferiority of PCI to CABG was defined as the upper limit of the 95% CI of the hazard ratio (HR) not exceeding 1·35 after 275 MACCE had occurred. Secondary endpoints included all-cause mortality, non-procedural myocardial infarction, and repeat revascularisation. Outcomes were analysed in the intention-to-treat population. This trial is registered with ClinicalTrials.gov, NCT01496651 . Findings: Between Dec 9, 2008, and Jan 21, 2015, 1201 patients were enrolled and allocated to PCI (n=598) or CABG (n=603), with 17 subsequently lost to early follow-up. 592 patients in each group were included in this analysis. At a median of 4·9 years of follow-up, the predefined number of events was reached for adequate power to assess the primary endpoint. Kaplan-Meier 5-year estimates of MACCE were 28% (165 events) for PCI and 19% (110 events) for CABG (HR 1·58 [95% CI 1·24–2·01]); the HR exceeded the limit for non-inferiority of PCI compared to CABG. CABG was found to be superior to PCI for the primary composite endpoint (p=0·0002). All-cause mortality was estimated in 9% after PCI versus 9% after CABG (HR 1·08 [95% CI 0·74–1·59]; p=0·68); non-procedural myocardial infarction was estimated in 8% after PCI versus 3% after CABG (HR 2·99 [95% CI 1·66–5·39]; p=0·0002); and repeat revascularisation was estimated in 17% after PCI versus 10% after CABG (HR 1·73 [95% CI 1·25–2·40]; p=0·0009). Interpretation: In revascularisation of left main coronary artery disease, PCI was associated with an inferior clinical outcome at 5 years compared with CABG. Mortality was similar after the two procedures but patients treated with PCI had higher rates of non-procedural myocardial infarction and repeat revascularisation. Funding: Biosensors.